Energetic Characteristics of HMX‐Based Explosives Containing LiH. Issue 6 (20th June 2016) - Ding, Xiao‐Yong; Shu, Yuan‐Jie; Liu, Ning; Wu, Min‐Jie; Zhang, Jian‐Guo; Gou, Bing‐Wang; Wang, Hai‐Min; Wang, Cai‐Ling; Dong, Shu‐Nan; Wang, Wei
Abstract: The high energy density compound octahydro‐1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocine (HMX) and the strong exothermic compound LiH represent an excellent principal explosive and an active fuel, respectively. Herein, the energetic characteristics of HMX‐based explosives are explored by adding LiH as fuel additive. The detonation parameters of HMX‐based explosives containing LiH were tested with free‐field explosion experiments and compared with those of traditional TNT, HMX, and aluminized explosives. The results show that the explosives exhibit higher energy and present preferable explosion effect when LiH is added as an explosive ingredient. The improvement of impulse is more than 32.8 % at 2 m. The shock wave peak overpressure increases by almost 40 % at a distance of 3 m from detonation center specially for the explosive containing both LiH and Al additives. Elemental H and Li are expected to release tremendous energy to effectively improve the explosives instant damage power, but the detonation duration is shorter than that of Al‐containing mixed explosives, which may limit the advantage over Al in the impulse. Li2 CO3 powder is the solid product of HMX/LiH, which explains the LiH oxidation during the explosion. The exothermic processes in the formation are the reason for the increased energy of HMX/LiH explosives. These results can provide guidance to a potential energetic system formed by HMX and LiH. Abstract :